2013
DOI: 10.1021/ed300384r
|View full text |Cite
|
Sign up to set email alerts
|

What Faculty Interviews Reveal about Meaningful Learning in the Undergraduate Chemistry Laboratory

Abstract: Forty chemistry faculty from American Chemical Society-approved departments were interviewed to determine their goals for undergraduate chemistry laboratory. Faculty were stratified by type of institution, departmental success with regard to National Science Foundation funding for laboratory reform, and level of laboratory course. Interview transcripts that were coded and analyzed using the lens of meaningful learning reveal the importance of cognitive and psychomotor goals relative to affective learning, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 14 publications
2
140
0
3
Order By: Relevance
“…Bretz (2001) classifies meaningful learning based on 3 criteria: (1) relevant prior knowledge of the student, (2) meaningful material organized by the teacher to connect to this prior knowledge, and (3) the conscious choice of the student to make connections between the prior knowledge and the new meaningful material. Integration between achievements of cognitive, affective and psychomotor domains can lead to meaningful learning (Bretz et al, 2013;DeKorver & Towns, 2015).In laboratory work, the psychomotor domain relies on the cognitive and affective domains (Galloway & Bretz, 2015). This is in line with current research which explains that human emotions are not limited to only one brain's area (Niedenthal, 2007; Touroutoglou et al, 2015).…”
supporting
confidence: 56%
“…Bretz (2001) classifies meaningful learning based on 3 criteria: (1) relevant prior knowledge of the student, (2) meaningful material organized by the teacher to connect to this prior knowledge, and (3) the conscious choice of the student to make connections between the prior knowledge and the new meaningful material. Integration between achievements of cognitive, affective and psychomotor domains can lead to meaningful learning (Bretz et al, 2013;DeKorver & Towns, 2015).In laboratory work, the psychomotor domain relies on the cognitive and affective domains (Galloway & Bretz, 2015). This is in line with current research which explains that human emotions are not limited to only one brain's area (Niedenthal, 2007; Touroutoglou et al, 2015).…”
supporting
confidence: 56%
“…With this in mind, researchers have demonstrated that undergraduate science students can increase their proficiency in communication and teamwork skills through active learning pedagogies and curriculum innovation (Pontin et al, 1993;Bailey et al, 2012;Mittendorf and Cox, 2013;Whittington et al, 2014). Many science professors will point to the laboratory portions of courses as a place where skills such as collaboration and communication are practiced (Lowery Bretz et al, 2013). Indeed, laboratory experiences can be used and are often used to satisfy accreditation requirements for transferable skills.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Our results indicate that faculty have two broad goals for the undergraduate chemistry curriculum. They want students to learn hands-on techniques (and know when it is appropriate to use them) and to improve their critical thinking skills.…”
Section: Faculty Goals For Laboratorymentioning
confidence: 69%
“…6 To address the gaps in the research that has been carried out in laboratory in 2005 we embarked with our collaborators on a research trajectory that would help us understand the goals that faculty and students have for laboratory. [7][8][9][10][11][12][13][14][15][16] The ultimate goal has been to describe the correspondence between the two and to shape and guide the laboratory curriculum in ways that would bring about a better correspondence.…”
Section: Role Of Laboratorymentioning
confidence: 99%